Infection Control in the Intensive Care Unit - Saene, Hendrick K.F.; Silvestri, Luciano; Cal, Miguel A.; Gullo, Antonino; SpringerLink (Online service) (Milano : Springer Milan, 2012)
Intensive care is a rapidly changing area of medicine; this third edition of "Infection Control in the Intensive Care Unit" has the same format as the previous one but covers a wider scope of infection prevention, from lower airways to bloodstream. This edition condenses and updates the information of the previous edition, with the addition of new tables and figures, and contains two completely new chapters on microcirculation and mechanisms of action behind the efficacy of Selective Decontamination of the Tract. SDD is an antimicrobial prophylaxis to prevent severe infections that has been proved to reduce inflammation; there is now evidence that SDD using parenteral and enteral antimicrobials reduces rather than increases antimicrobial resistance. Latest results are here taken into account; 10 new randomised controlled trials and 2 recent meta-analyses with endpoints of multiple organ failure and resistance. The outbreak chapter is substantially reduced and builds on the previous issue; it now includes polyclonality within outbreaks. This up-to-date and comprehensive study will be welcomed by intensive care specialists, clinical microbiologists, infection disease specialists and clinical pharmacists who wish to learn about the most recent discoveries and advances in infection control. It will also be of interest to advanced undergraduates wanting to learn more about the subject.
Foreword-Preface -- Section 1: Essentials in Clinical Microbiology -- Section 2: Antimicrobials -- Section 3: Infection Control -- Section 4: Infections on ICU -- Section 5: Special Topics.
Keywords: Medicine; Microbiology; Drug interactions; Pharmacy; Critical care medicine; Internal medicine; Medicine & Public Health; Intensive / Critical Care Medicine; Internal Medicine; Pharmacy; Medical Microbiology; Drug Resistance